Leadership and its impact on educational institutions: a systematic review - Huangal-Scheineder, Sebastián; Cieza-Sánchez, Jaime; Diaz-Paredes, Manuel; Arriaga-Delgado, Miguel; Marchena-Tafur, Aurora (International Journal of Evaluation and Research in Education (IJERE), 2024)
Leadership, in the educational field, is an important tool to improve the functioning of an educational institution and student learning. For this, trained leaders are required to exercise the most appropriate changes and manage the joint work of workers, in order to meet the proposed goals. In this context, this work had the objective of this article was to explore the role of directors and teachers in achieving the objectives of educational institutions, identify the most recommended leadership style for educational institutions, and identify the importance of having strong leadership within them. With this aim in mind, a systematic review of the literature based on the PRISMA method was carried out, selecting 50 publications. As a result, it was concluded that good leadership is fundamental for the academic development of institutions at any educational level, and that much of this responsibility falls on managers. In addition, the transformational leadership style is highlighted as the most effective to be used within schools and universities, and to provide a better educational experience for students.